Ecology of southern European pearl mussels (Margaritifera margaritifera): first record of two new populations on the rivers Terva and Beça (Portugal) - Varandas, Simone (2013)
1. Southern European populations of Margaritifera margaritifera (L., 1758) are under-studied. From 1986 to 2001 this species was considered extinct in Portugal but between 2001 and 2002 six northern populations were found, five of which were previously unknown. 2. This study comprises a comparative study of the ecology and habitat requirements of two new populations in the rivers Beça and Terva (tributaries of the River Tâmega, northern Portugal) with non-Iberian populations. 3. Surveys were conducted in 2010/2011 to characterize ecological status and propose possible conservation measures. Both rivers were in good environmental condition, but the River Beça had higher biological, physicochemical and hydromorphological quality. 4. Both populations are highly susceptible to extirpation – in particular the River Terva population, given the very low number of specimens found and no sign of recent recruitment. The low number of juveniles and the existence of several threats in both rivers (e.g. fragmentation and loss of habitat caused by the presence of physical obstacles, organic pollution and bank erosion due to fires) imply the need for urgent, effective, conservation measures. 5. Southern European M. margaritifera populations have similar ecological and habitat requirements compared with those of northern and central Europe. However, functional populations may endure higher phosphate content, pH and temperature values. As expected they present faster growth rates and reduced life spans.